Raciocínios morais de justiça e de perdão em Padres - Silva, Frankleudo Luan de Lima (2018)
Increasingly, psychology studies have shown that religious experience is a relevant factor for the moral development of the individual, however, such investigations have been particularly lax in the more rigorous analyzes of the foundations of this relationship. onsidering specifically the universe of Catholicism and shedding light on justice and forgiveness as moral and developmental virtues, the thesis is argued here that the moral reasoning of justice and pardon of priests is supported by the guidelines doctrine of the Catechism of the Catholic Church concerning justice and forgiveness. This is because the doctrinal force preserved in the Catechism, the text of the essential contents regarding faith and morals in the Catholic sphere, seems to guide the moral progress of its followers. This thesis is structured in two studies: a study of the conceptions of justice and forgiveness contained in the Catechism of the Catholic Church and an empirical study of the moral reasoning for justice and forgiveness of Catholic priests. Two theories served as the primary basis for the empirical study: Lawrence Kohlberg's theory of the development of justice, and Robert Enright's theory of the development of the reasoning for forgiveness. Each author presents a typology of stages, which represent the complexity of reasoning in the face of moral decisions. In addition, philosophical and theological reflections were developed in order to give greater intelligibility to the analyzes carried out. The study of excerpts referring to justice and forgiveness present in the Catechism was conducted through the analysis of thematic categorical content, indicating that the church evokes four majoritarian conceptions about justice, which are interconnected and are expressed in isolation: divine rectoral justice, distributive justice, commutative justice, and social justice. As for conceptions of forgiveness, the Catechism presents three main conceptions: forgiveness as participation in divine grace, forgiveness as recognition of human fallibility, and forgiveness as an expression of compassionate love. From the empirical study, 30 priests from the Archdiocese of Paraíba participated. As instruments, a bioemographic questionnaire and a questionnaire composed of two moral dilemmas were used, the first one aimed at identifying the dominant stages of the thought of justice and the second one aimed at identifying the dominant stages of the reasoning of forgiveness. The predominant use of justice reasoning based on the valorisation of the obedience to the law or the conventions for the maintenance of the social order (stage 4 in Kohlberg's typology) and reasoning based on the understanding that people have individual rights, it being possible, through legal channels and democratic agreements, to change laws or morals that are eventually unjust (stage 5). Both reasonings find support in catechetical orientations, which can both elicit strictly legalistic thoughts and reasonings that transcend the conventional limit of law. For the reasoning of forgiveness, stages 3 (in the Enright classification) were dominant, which is in line with the expectations of the belonging group; followed by stage 2.5, based on moral compensation exemplified in the apology and attitudinal change of the offender. These reasonings follow in the direction of the idea, evidenced by the Catechism, that forgiveness is the recognition of error, the excuses, the visible signs of repentance, and the commitment to change of behavior. Spearman's correlation test has shown a significant relationship between reasoning of justice and reasoning for forgiveness, indicating that when the thought of justice advances, the thought of forgiveness also advances to some degree. Through a non-parametric test of Mann Whitney U, it has been found that priests who coordinate parishes with active, socially engaged pastoral programs present more advanced reasoning and justice reasoning, presumably to know and consider the needs attenuating circumstances and the perspective of people before issuing judgments of justice and forgiveness. Regarding the content of the answers of the priests on the question "What does justice mean?", The most frequent categories - "equality", "rights and duties", "complying with the law" and "social balance" - are aligned with the constant conceptions of justice in the doctrinal text of the Catechism of the Catholic Church and corroborate the predominance of the use of stages 4 and 5 of thought of justice, based, respectively, on the enthronement of the law as an inviolable entity and on the reworking of laws, through democratic contractual procedures, in order to to maximize overall well-being. Regarding the answers to the question "What does it mean to forgive?", Most priests, in keeping with the conceptions of forgiveness evoked by the Catechism, emphasized the reduction / interruption of negative feelings and affections elicited by heartache, recognition of the fallible nature of human, forgiveness as a credit of trust and as an attitude that expresses love, giving and compassion. In general, we identified a great compatibility between the reasoning of the participants and the discursive content of the catechetical text, suggesting the confirmation of the thesis proposed in the present study.